2018
DOI: 10.1002/slct.201702691
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Thiocarbohydrazones: Experimental Studies and Alignment‐Independent 3D QSAR Models

Abstract: Due to the rise of microbial strains resistant to conventional therapies, there is an urgent need for finding the new antimicrobial chemotypes. Heterocyclic compounds such as thiocarbohydrazones (TCHs) are able to interact with many metalloenzymes essential for microbes, while sulfur atom increases lipophilicity which is generally positively correlated with potency. In this paper, we report antibacterial and antifungal activity of twenty-two TCHs toward eight bacterial and three fungal strains. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition to the solvent effect, results of the correlations of the absorption maxima with Hansen's Fig. 9 ICT processes in E isomers of monothiocarbohydrazones (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Left images, difference between densities in first excited and ground state (red and blue, density increase and decrease upon transition, respectively); right images, positions of barycenters for charge loss (cyan circle) and charge gain (violet circle) upon transition solubility parameters showed that the dispersion forces are the most dominant interactions between the examined mTCHs and the surrounding medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the solvent effect, results of the correlations of the absorption maxima with Hansen's Fig. 9 ICT processes in E isomers of monothiocarbohydrazones (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Left images, difference between densities in first excited and ground state (red and blue, density increase and decrease upon transition, respectively); right images, positions of barycenters for charge loss (cyan circle) and charge gain (violet circle) upon transition solubility parameters showed that the dispersion forces are the most dominant interactions between the examined mTCHs and the surrounding medium.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the molar ratio of the reactants (1:1 or 1:2), mono-or bis-substituted thiocarbohydrazones can be obtained [1,2]. Many of these compounds tested so far have shown exceptionally good antimicrobial [3][4][5], antioxidant [6,7], and antitumor [8,9] activity. Due to their structure, more specifically to the presence of nitrogen and sulfur atoms, they are easily coordinated and can build complexes with many transition metals [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Božic et al explored the antimicrobial activity of twenty-two mono-and bisthiocarbohydrazones derived from 2-acetylpyridine and related carbonyl compounds (9-11, Scheme 4) [54]. The antibacterial activity was evaluated using four different strains of Gram-positive bacteria (Bacillus subtilis, Staphylococcus aureus, Clostridium sporogenes and Kocuria rhizophila) and four different strains of Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa, Proteus hauseri and Salmonella enterica subsp.…”
Section: Symmetric Thiocarbohydrazones Derived From Pyridyl and Relatmentioning
confidence: 99%
“…In a comparison with symmetric TCHs (see previous section), quinolyl and pyridyl mono TCHs (22-24, Scheme 8) were tested for both their antitumor [52] and antimicrobial activity [54]. In the former report, mono-TCHs treatments induced considerably higher pro-oxidative activity compared to their bis-structural analogues; the increased pro-oxidant capacity was probably related to the terminal hydrazide group.…”
Section: Asymmetric Thiocarbohydrazones Derived From Pyridyl and Relamentioning
confidence: 99%
“…Among their biological activities are antibacterial, anticancer, antifungal, anti-inflammatory, antimycobacterial, antioxidative, antituberculosis, and herbicidal activities. Furthermore, thiocarbohydrazones are utilized as starting materials in the synthesis of industrial and biological compounds with the potential of developing a new class of antileishmanial compounds [8][9][10]. The fungicidal activity of thiocarbohydrazones has been tested on textile fabrics [11], and recently, the synthesis and investigation of a series of 2-acetylpyridine thiocarbohydrazones as inactivators of Herpes simplex virus-1 (HSV-1) ribonucleotide reductase showed better results compared to analogous 2-acetylpyridine thiosemicarbazone derivatives [12].…”
Section: ■ Introductionmentioning
confidence: 99%